Estudo da influência de tensoativos em sistemas microemulsionados na extração de gálio e alumínio - Lucena Neto, Marciano Henrique de (2005)
Gallium is an important material used in the electronic industry whose demand in the world market is increasing in view of its potential applications. A selective technique is required to allow for the production of the metal, separated from aluminium. Due to the fact that microemulsions constitute an attractive alternative to metal extraction procedures, microemulsified systems have been employed as gallium-selective extraction agents. Two surfactants have been synthesized: sodium 12-N,N-diethylamino-9,10-dihydroxyestearate (AMINE) and saponified coconut oil (SCO), both produced from raw materials readily available in Northeastern Brazil. Also, the commercial extraction agent KELEX-100, conventionally used with the same purpose, has been used in this work for comparison. The optimization of the extraction process with microemulsions was carried out by investigating the influence of some parameters, namely the type of cosurfactant, the cosurfactant/surfactant (C/S) ratio, the pH and concentration of metals in the aqueous phase. Pseudoternary diagrams, which are representative of the microemulsified systems under study, have been constructed in order to establish the boundaries of the regions where the several Winsor systems are formed. An experimental planning methodology (Scheffé Net) has been used to optimize the extraction. The extraction percentage values were as high as 100% for gallium and 99.99% for aluminium for the system with KELEX-100; 96.6% for gallium and 98.8% for aluminium for the system containing AMINE; and 88% for gallium and 85% for aluminium for the system with SCO. The microemulsified system chosen for presenting the best results in gallium extraction was composed by SCO/isoamyl alcohol/kerosene/Bayer licquor with a C/S ratio of 28 and pH of the original aqueous phase of 6.0. The selectivity that has not been observed in the extraction stage was accomplished in the reextraction process using HCl. For the KELEX-100 system, gallium was reextracted at 100% with 6M HCl and aluminium was reextracted at 100% with 0.8M HCl. For the AMINE system, the reextraction percentages were also 100% for both metals, using 6M HCl for gallium and 0.5M HCl for aluminium. On the other hand, the reextraction percentages for the system with SCO were as high as 84% for gallium and 92% for aluminium, with HCl in the same concentrations as those used in the AMINE system. Finally, an optimized system was applied in the gallium extraction process employing a reciprocating perforated-plates extractor. As a result, the metal content was extracted at a recovery rate of 95% for gallium and 97% for aluminium